The theory-practice gap of black carbon mitigation technologies in rural China. (February 2018) - Zhang, Weishi; Li, Aitong; Xu, Yuan; Liu, Junfeng
Abstract: Black carbon mitigation has received increasing attention for its potential contribution to both climate change mitigation and air pollution control. Although different bottom-up models concerned with unit mitigation costs of various technologies allow the assessment of alternative policies for optimized cost-effectiveness, the lack of adequate data often forced many reluctant explicit and implicit assumptions that deviate away from actual situations of rural residential energy consumption in developing countries, where most black carbon emissions occur. To gauge the theory-practice gap in black carbon mitigation – the unit cost differences that lie between what is estimated in the theory and what is practically achieved on the ground – this study conducted an extensive field survey and analysis of nine mitigation technologies in rural China, covering both northern and southern regions with different residential energy consumption patterns. With a special focus on two temporal characteristics of those technologies – lifetimes and annual utilization rates, this study quantitatively measured the unit cost gaps and explain the technical as well as sociopolitical mechanisms behind. Structural and behavioral barriers, which have affected the technologies' performance, are discussed together with policy implications to narrow those gaps. Highlights: Black carbon mitigation technologies could cost more in practice than in theory. We quantify the theory-practice unit cost gaps in rural China. First-hand rural household survey was conducted on residential energy consumption. Two temporal factors, lifetimes and annual utilization rates, led to the gaps. Sociopolitical mechanisms are discussed for understanding and narrowing the gaps.